Prognostic role of progesterone receptor (PR) expression by immunohistochemistry (IHC) in relation to Oncotype recurrence scores (RS). - Basaran, Gul; Korkmaz, Taner; Kara, Halil; Boler, Deniz; Kapucuoglu, Nilgun; Uras, Cihan; Saglican, Yesim; Ince, Umit (AMER SOC CLINICAL ONCOLOGY, 2015)
Annual Meeting of the American-Society-of-Clinical-Oncology (ASCO) / Clinical Science Symposium on Predicting and Improving Adverse Outcomes in Older Adults with Cancer, Chicago, IL, MAY 29-JUN 02, 2015